PENGARUH WORK STRESS TERHADAP WORK ENGAGEMENT DENGAN JOB SATISFACTION SEBAGAI MEDIASI - Puspitasari, Triastika; Adi, Agung Nugroho (Jurnal Kewirausahaan dan Inovasi, 2023)
The objective of this quantitative causal research is to analyze the mediating role of job satisfaction in the effects of work stress on work engagement. This study was conducted due to the gap phenomenon in the research subject, PT INKA Multi Solusi. The results of the past annual survey demonstrate a decreasing trend in work engagement and job satisfaction despite the decreasing work stress level. Using Slovin formula, the number of the sample was set to 100 respondents; they were selected through simple random sampling from five departments representing all directorates. The departments are Information Technology, Cooling System & Non-Train, Company Secretary, Logistics, and Risk Management. The research data was harvested via questionnaires and was analyzed using Partial Least Squares in SmartPLS. This study finds that (1) work stress insignificantly influences work engagement, (2) that work stress negatively and significantly impacts job satisfaction, (3) that job satisfaction positively and significantly affects work engagement, and that (4) job satisfaction mediates the effect of work stress on work engagement. This study offers a deeper understanding about the mechanism of influence between the variables through the perspective of Job Demands-Resource Theory (JD-R). The practical implication of this research is that the company must focus on job satisfaction first so that work stress can be contained in order to increase work engagement.